Pediatric Burn Survivors Have Long-Term Immune Dysfunction With Diminished Vaccine Response - Johnson, Blair Z.; McAlister, Sonia; McGuire, Helen M.; Palanivelu, Vetrichevvel; Stevenson, Andrew; Richmond, Peter; Palmer, Debra J.; Metcalfe, Jessica; Prescott, Susan L.; Wood, Fiona M.; Fazekas de St Groth, Barbara; Linden, Matthew D.; et al. (Frontiers in Immunology, 2020)
Epidemiological studies have demonstrated that survivors of acute burn trauma are at long-term increased risk of developing a range of morbidities. The mechanisms underlying this increased risk remain unknown. This study aimed to determine whether burn injury leads to sustained immune dysfunction that may underpin long-term morbidity. Plasma and peripheral blood mononuclear cells were collected from 36 pediatric burn survivors >3 years after a non-severe burn injury (<10 % total body surface area) and from age/sex-matched non-injured controls. Circulating cytokine and vaccine antibody levels were assessed using multiplex immunoassays and cell profiles compared using a panel of 40 metal-conjugated antibodies and mass cytometry. TNF-α (1.31-fold change from controls), IL-2 (1.18-fold), IL-7 (1.63-fold) and IFN-γ (1.18-fold) were all significantly elevated in the burn cohort. Additionally, burn survivors demonstrated diminished antibody levels to the diphtheria, tetanus, and pertussis vaccine antigens. Comparisons between groups using unsupervised clustering identified differences in proportions of clusters corresponding to naïve and memory T-cell subsets, and subpopulations of B-cells and myeloid dendritic cells. Manual gating confirmed increased memory T-regulatory, and central memory CD4+ T-cells, with altered expression of T-cell, B-cell, and dendritic cell markers. Conclusions: This study demonstrates a lasting change to the immune profile of pediatric burn survivors that traverses innate and adaptive immunity, and highlights the need for further research into post-burn immune suppression and regulation.